Intracranial Germinomas: Diagnosis, Pathogenesis, Clinical Presentation, and Management - Kremenevski, Natalia; Buchfelder, Michael; Hore, Nirjhar (Current oncology reports, 2023)
Purpose of Review Intracranial germinomas constitute a rare brain tumor entity of unknown etiology, characterized by unique histopathology and molecular biology. In this manuscript, we review the literature focusing on the epidemiology, histopathology with molecular biology, clinical presentation with emphasis on tumor location, diagnostic workup, and current treatment strategies with related clinical outcomes of intracranial germinomas. Recent Findings Although the optimal treatment strategy remains a matter of debate, intracranial germinomas respond well to radiotherapy, chemotherapy, or a combination of both and are characterized by very high cure and survival rates. It is well-known that early discrimination of germinomas from other intracranial neoplasms facilitates the timely initiation of appropriate treatment, thereby contributing to the reduction of morbidity as well as mortality. Summary Ongoing research will need to be directed towards discovering and refining reliable parameters for early diagnosis and evaluation of prognosis in patients with intracranial germinomas.